2022
DOI: 10.1002/mrm.29320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inversion methods inMRelastography: An open‐access pipeline for processing multifrequency shear‐wave data and demonstration in a phantom, human kidneys, and brain

Abstract: Purpose Magnetic resonance elastography (MRE) maps the viscoelastic properties of soft tissues for diagnostic purposes. However, different MRE inversion methods yield different results, which hinder comparison of values, standardization, and establishment of quantitative MRE markers. Here, we introduce an expandable, open‐access, webserver‐based platform that offers multiple inversion techniques for multifrequency, 3D MRE data. Methods The platform comprises a data repository and standard MRE inversion methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…SWS and PR maps were reconstructed based on 2D phase gradients. The 2D pipeline is publicly available on https://bioqic-apps.charite.de/ (Meyer et al, 2022). For 3D data processing, slice phase offsets and interphase discontinuities between slices were removed after temporal Fourier transform according to Barnhill et al (2019).…”
Section: Mre Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…SWS and PR maps were reconstructed based on 2D phase gradients. The 2D pipeline is publicly available on https://bioqic-apps.charite.de/ (Meyer et al, 2022). For 3D data processing, slice phase offsets and interphase discontinuities between slices were removed after temporal Fourier transform according to Barnhill et al (2019).…”
Section: Mre Data Analysismentioning
confidence: 99%
“…On the other hand, 2D inversion algorithms are less prone to interslice artifacts and do not require multi-slice acquisitions, which expedites image acquisitions of thinner slabs through the tissue of interest (Tzschatzsch et al, 2016;Mura et al, 2020). To tackle the longstanding question of whether 2D or 3D MRE is preferable for intracranial applications we developed a brain processing pipeline which exploits wavenumber (k)-based multifrequency dual elasto-visco (k-MDEV) inversion in two variants, once as a new development with shear wave separation in 3D using the curl operator and once with 2D bandpass filtering (Herthum et al, 2022a;Herthum et al, 2022b) [publicly available (Meyer et al, 2022)]. k-MDEV supports multifrequency inversion as included in the tomoelastography pipeline that has been used in many multifrequency MRE applications in abdominal and pelvic organs (Dittmann et al, 2017;Shahryari et al, 2019;Reiter et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRE data were processed in MATLAB Release 2021a (The Mathworks Inc. Natick, MN, United States) using wavenumber-based inversion method (k-MDEV) ( Tzschätzsch et al, 2016 ) publicly available at https://bioqic-apps.charite.de ( Meyer et al, 2022b ). A Butterworth low-pass filter of order 3 with a threshold of 250 m −1 was used to suppress noise prior to image unwrapping ( Herthum et al, 2022 ) while a spatial bandpass Butterworth filter of order 3 with thresholds of 15 m −1 and 300 m −1 was used for directional filtering ( Herthum et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The variety in the acquisition conditions and in the type of tissue or organ under study, 3 and the lack of appropriate reference measurements, are all factors that have somewhat obscured the proper comparison of the relative merits of each reconstruction. In the brain or in the kidney, different reconstructions have been compared, and it was found that mean stiffness values could differ significantly between the tested reconstructions 7,8 . In the liver, reports have compared the relative performances obtained with different reconstruction algorithms, but in several cases, the reconstruction algorithms were not compared on identical source data 9–11 .…”
mentioning
confidence: 99%